2011
DOI: 10.1021/es2022818
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Policy Relevant Background (PRB) Ozone Concentrations in the United States

Abstract: Policy Relevant Background (PRB) ozone concentrations are defined by the United States (U.S.) Environmental Protection Agency (EPA) as those concentrations that would occur in the U.S. in the absence of anthropogenic emissions in continental North America (i.e., the U.S, Canada, and Mexico). Estimates of PRB ozone have had an important role historically in the EPA's human health and welfare risk analyses used in establishing National Ambient Air Quality Standards (NAAQS). The margin of safety for the protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 67 publications
4
53
1
1
Order By: Relevance
“…Global modeling studies have reported high-O 3 bias simulated in air arriving along the Texas coast (Fiore et al, 2002(Fiore et al, , 2014McDonald-Buller et al, 2011;Zhang et al, 2011). The high-O 3 bias over 10 ppb has been reported by a regional modeling study (Sarwar et al, 2015;Smith et al, 2015).…”
Section: Regional Mpe Analysis At Remote Sites Along the Gulf Coastmentioning
confidence: 75%
“…Global modeling studies have reported high-O 3 bias simulated in air arriving along the Texas coast (Fiore et al, 2002(Fiore et al, , 2014McDonald-Buller et al, 2011;Zhang et al, 2011). The high-O 3 bias over 10 ppb has been reported by a regional modeling study (Sarwar et al, 2015;Smith et al, 2015).…”
Section: Regional Mpe Analysis At Remote Sites Along the Gulf Coastmentioning
confidence: 75%
“…Earlier reviews synthesize observations relevant for evaluating base model simulations at remote sites (McDonald-Buller et al, 2011;Reid et al, 2008;Vingarzan, 2004). Even with the same approach, model estimates will differ due to different representations of natural emissions and the choice of different years since meteorological variability alters the balance between transported vs. regionally produced O 3 .…”
Section: Review Of Prior Model Estimates For Nab and Its Componentsmentioning
confidence: 99%
“…It is an important quantity for policy as it represents a floor below which air quality cannot be improved by eliminating emissions in the US, Canada, and Mexico. The North American background is not an observable quantity and must therefore be estimated from models (McDonald-Buller et al, 2011). A number of studies have been conducted for this purpose, based on the GEOS-Chem global chemical transport model (CTM) (Fiore et al, 2003;Wang et al, 2009; and the CAMx regional model with GEOS-Chem boundary conditions (Emery et al, 2012).…”
Section: Zhang Et Al: Sources Contributing To Background Surface mentioning
confidence: 99%